Pengaruh Dana Desa dan Alokasi Dana Desa Terhadap Tingkat Kemiskinan di Kecamatan Sitinjau Laut Kab. Kerinci - Herlina, Vivi (Haka Vyza Media, 2025)
The purpose of this study is to analyze the effect of Village Funds (DD) and Village Fund Allocation (ADD) on the poverty rate in Kec. Sitinjau Laut District, Kab. Kerinci. The data used are secondary data consisting of poverty rate data, Village Fund data and Village Fund Allocation data in 2024. The analysis method used is multiple linear regression which is then analyzed for the magnitude of partial influence and also simultaneous influence. The results of the partial test showed that there was no significant effect between Village Funds and Village Fund Allocation on the Poverty Rate, while the results of the simultaneous test showed that there was no significant effect between Village Funds and Village Fund Allocation on the Poverty Rate in Kec. Sitinjau Laut.